2010
DOI: 10.2319/110109-612.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy effects in traumatized permanent teeth with extrusive luxation in an orthodontic patient

Abstract: The aim of this case report was to present and evaluate the effect of low-level laser therapy on traumatized permanent teeth with extrusive luxation in an orthodontic patient. The treatment and follow-up evaluation of two orally luxated maxillary permanent central incisors in a 19-year-old man is described. Detailed anamnesis was taken, and extraoral, intraoral, radiographic examinations and electrical and thermal pulpal tests were performed to determine the type of the luxation and the further treatment proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this way, a surgical wound healing that is free-infection and with reduced presence of inflammation and pain is extremely necessary. 6 21 22 Furthermore, the presence of laser device reduces the perception of fear in the patients, thus, encourage a positive attitude toward the dental treatment. 15 The results exhibited in this study is in agreement of a previous approach that suggested the laser treatment results in minimum or nether postoperative swelling nor pain with less discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, a surgical wound healing that is free-infection and with reduced presence of inflammation and pain is extremely necessary. 6 21 22 Furthermore, the presence of laser device reduces the perception of fear in the patients, thus, encourage a positive attitude toward the dental treatment. 15 The results exhibited in this study is in agreement of a previous approach that suggested the laser treatment results in minimum or nether postoperative swelling nor pain with less discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] For extrusive laxative traumatic dental injuries of permanent teeth that exceed two millimeters, laser management has been previously introduced as an efficacious modality that can effectively replace the endodontic management modalities. 31 Delayed or ignored early repositioning of the affected teeth might lead to the development of serious complications leading to reduced crown to root ratio and decreased support of the surrounding bony structures. Moreover, this will even make it harder for orthodontists to draw the appropriate management modality of this trauma.…”
Section: Intrusion and Extrusion Luxationmentioning
confidence: 99%
“…If there is any tooth mobility then the examination for the concerned tooth has to be done in both a horizontalas well as vertical direction. 15 4. During the clinical examination palpation over the tooth apex for tenderness should be checked.…”
Section: Significant Risk Factors Due To Dental Trauma 11mentioning
confidence: 99%